THEORETICAL EVALUATION OF NEW DERIVATIVES OF THE TETRAHEDRANE NITRATOXYCARBON - G. Calvo, Luis (2015)
We calculated the properties of nitratoxycarbon tetrahedrane derivatives using the methods:Hartree-Fock and density functional theory. We assessed structure, the electronic propertiesand energy profile to show Mulliken population analysis that the increase of nitratoxycarbongroups reduce the burdens of the oxygen’s of the group substituent.